PENGOLAHAN HIJAUAN PAKAN KALKUN DI PETERNAKAN KALKUN KECAMATAN UNDAAN, KABUPATEN KUDUS - Utama, Cahya Setya; Wicaksono, M. I. (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2021)
This research aims to examine the application of turkey forage processing technology to the productivity of the turkey. The observed materials were turkey in Undaan District, Kudus Regency; the feed ingredients were CP 511 commercial feed, forage in the form of water hyacinth, and rice bran. The research method is descriptive. There is purposive random sampling to represent the size of the research area. It applies in 15 breeders on Undaan District as the samples. The research variables are the application of forage processing technology of the turkey farmer and the productivity of the turkey. The result is that the turkey breeders in Undaan generally have mechanical processing on a forage. The forages were chopped with a forage-chopper machine or a knife manually. The forage processing was started by chopping the water hyacinth, then added the concentrate and the bran with the ratio 6:1:3. All of the components were mixed in a bucket with 40 liters capacity. The conclusion is that the turkey breeders applied a simple technology by chopping the forage components with a forage-chopper machine or a knife manually. The forage, that consists of water hyacinth, concentrates, and additives, can increase the turkey productivity.